Highly Enhanced Photocatalytic Water-Splitting Activity of Gallium Zinc Oxynitride Derived from Flux-Assisted Zn/Ga Layered Double Hydroxides - Yang, Jae Hun; Pei, Yi Rong; Kim, Seung Joo; Choi, Goeun; Vinu, Ajayan; Choy, Jin Ho (Industrial and Engineering Chemistry Research, 2018)
The Ga/Zn oxynitride solid solution [(GaN)1-x(ZnO)x] is one of the promising visible light harvesting photocatalysts for overall water splitting. A series of (GaN)1-x(ZnO)x (0.11 ≤ x ≤ 0.33) compounds are synthesized by calcining the carbonate-type Zn/Ga-LDH precursor with and without sodium carbonate flux at 850 °C for 8-14 h under a NH3 gas flow. The solid solutions without flux are determined to be low in crystallinity, but platelike morphology with preferred orientation could be observed. On the other hand, those with flux turn out to be better in crystallinity, and eventually exhibit significantly higher photocatalytic activity for overall water splitting under visible light irradiation than those without flux. In addition, the band gap energies can also be engineered from 2.57 to 2.72 eV by changing a synthetic parameter such as nitridation time. It is, therefore, suggested that the present new approach can offer new opportunities for designing the next generation of photocatalytic systems.
Keywords: Layered double hydroxides; Photocatalytic activities; Photocatalytic systems; Photocatalytic water splitting; Plate-like morphology; Preferred orientations; Synthetic parameters; Visible-light irradiation